Multidrug-resistant tuberculosis in Finland: treatment outcome and the role of whole-genome sequencing. Issue 4 (28th November 2022) - Korhonen, Virve; Kivelä, Pia; Haanperä, Marjo; Soini, Hanna; Vasankari, Tuula
Treatment of multidrug-resistant tuberculosis (MDR-TB) is a global challenge requiring long treatment with costly drugs. We assessed treatment combinations, outcome and the utility of whole-genome sequencing (WGS) in MDR-TB cases. Clinical, demographic and microbiological data were obtained of all patients with MDR-TB who started treatment in Finland in 2007–2016. Definitions of MDR, pre-extensively drug-resistant (pre-XDR) and XDR tuberculosis were those applicable at the study period. Treatment outcome was defined according to World Health Organization (WHO) guidelines. Mycobacterium tuberculosis isolates were analysed by WGS in addition to routinely performed phenotypic drug susceptibility testing and genotyping. Among the 47 cases, 35 (74%) had a successful treatment outcome. Risk factors for non-successful outcome were Finnish origin and XDR. Almost 90% of our cases had an adverse event for at least one drug. Phenotypic and WGS drug resistance results were fully concordant for isoniazid, fluoroquinolones and amikacin, and >90% concordant for rifampicin, pyrazinamide, kanamycin and capreomycin. >60% of phenotypically ethambutol-susceptible isolates were genotypically resistant. The results of the rifampicin and isoniazid nucleic acid amplification tests (NAATs) performed for the isolates were identical to the WGS results except for three isolates having uncommon resistance mutations not included in the NAATs. WGS did not reveal unexpected clustering. More training is needed for physicians treating MDR-TB, and especially XDR-TB, to improve treatment outcome. Phenotypic drug susceptibility testing was shown to be unreliable for ethambutol. WGS could aid in the selection of optimal treatment regimen in the future. In Finland, the success rate of individualised MDR-TB treatment is 74%, despite numerous adverse effects. Whole-genome sequencing could aid in the selection of optimal treatment regimen in the future. https://bit.ly/3fnMYfY